Parental Perspectives in Holistic Assessment: Understanding Primary School Students’ Comprehensive Development - Sahoo, Sanjukta (JOURNAL OF INDIAN EDUCATION, 2026)
Holistic assessment in primary education has gained prominence as educators recognise the need to evaluate students’ comprehensive development beyond academic achievements. Parental perspectives are crucial for understanding a child’s cognitive, social, emotional, and physical development. This study explores the significance of parental perspectives in holistic assessment to understand primary school students’ overall development. The study aims to examine parental involvement, perceptions, and expectations related to holistic assessment through the descriptive survey method. Data were collected using a self-constructed 5-point Likert scale from 40 parents whose children attended government-aided primary schools in Belda, Paschim Medinipur, West Bengal, India. The findings indicate that 60 per cent of parents reported low participation in school activities, while 67.5 per cent felt uncomfortable communicating with teachers. However, 67.5 per cent agreed that a holistic assessment approach is essential for their child’s overall development, and 85 per cent expected collaboration with schools in creating individualised development plans. The study highlights the need for enhanced parental involvement, effective communication, and structured collaboration between schools and parents to improve holistic assessment practices.